Profiling perpetrators of interpersonal violence against children in sport based on a victim survey. (January 2017) - Vertommen, Tine; Kampen, Jarl; Schipper-van Veldhoven, Nicolette; Wouters, Kristien; Uzieblo, Kasia; Van Den Eede, Filip
Abstract: The current article reports on perpetrator characteristics gathered in the first large-scale prevalence study on interpersonal violence against children in sport in the Netherlands and Belgium. Using retrospective web survey design, 4043 adults answered questions on their experiences in youth sport. The study looks at the number of perpetrators as well as individual descriptive characteristics (sex, age, and role in the sport organization) of perpetrators of psychological, physical and sexual violence as reported retrospectively by victim-respondents. This information was then clustered to provide an overview of the most common perpetrator profiles. Results show that in all types of interpersonal violence in sport, perpetrators are predominantly male peer athletes who frequently operate together in (impromptu) groups. Several differences between the three types of interpersonal violence are highlighted. While incidents of physical violence perpetrated by coaches tend to be less severe compared to those by other perpetrators, acts of sexual violence committed by a coach are significantly more severe. The presented findings shed new light on perpetrators of interpersonal violence in sport, nuancing the predominant belief that the male coach is the main perpetrator while providing nuanced information that can be utilized to improve prevention and child protection measures and other safeguarding initiatives in sport.